The nativization of verb–noun collocations in Pakistani English. - Afzal, Saima; Ang, Leng Hong; Abdul Rahim, Hajar (World Englishes, 2026)
This study examines an under–explored feature of Outer Circle Englishes: the nativization of verbnoun collocations in written Pakistani English (PakE). Using a 5–million–word Pakistani Acrolectal Variety of English corpus, with the British National Corpus 2014 as a reference, statistically salient constructions were identified using mutual information and Log Dice. The analysis examines six entrenched verbnoun collocations: take notice, seek a report, register a case, recover (abducted persons), produce (person) before court, and award (a) sentence. The findings show that these collocations coalesce into a procedural scripta nativized template that serializes institutional action from initiation to sanction. The study further demonstrates how linguistic transfer from Urdu and socio–institutional practices shape these patterns, producing systematic formal and contextual distinctiveness. These results support the emergence of a legitimized institutional register in PakE and advance understanding of nativization in postcolonial Englishes, with implications for ESL pedagogy and language policy.